Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.5194/gchron-3-171-2021
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Driftwood provides reliable chronological markers in Arctic coastal deposits

Abstract: Abstract. Originating from the boreal forest and often transported over large distances, driftwood characterizes many Arctic coastlines. Here we present a combined assessment of radiocarbon (14C) and dendrochronological (ring width) age estimates of driftwood samples to constrain the progradation of two Holocene beach-ridge systems near the Lena Delta in the Siberian Arctic (Laptev Sea). Our data show that the 14C ages obtained on syndepositional driftwood from beach deposits yield surprisingly coherent chrono… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Alternatively, the wood may have stayed an unusually long time in seawater, which modified its 14 C composition. However, this hypothesis seems unlikely as supported by our study's results and those of other arctic driftwood radiocarbon dating which are in agreement with dendrochronological dates and radiocarbon dating of terrestrial mammal bones, and have been long used to date beach ridges formation systems (see Sander et al, 2021;Taïeb et al, 2022). The same argument applies to the possible effect of permafrost burial in time.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Alternatively, the wood may have stayed an unusually long time in seawater, which modified its 14 C composition. However, this hypothesis seems unlikely as supported by our study's results and those of other arctic driftwood radiocarbon dating which are in agreement with dendrochronological dates and radiocarbon dating of terrestrial mammal bones, and have been long used to date beach ridges formation systems (see Sander et al, 2021;Taïeb et al, 2022). The same argument applies to the possible effect of permafrost burial in time.…”
Section: Resultssupporting
confidence: 88%
“…the Yukon and Kuskokwim rivers in Interior Alaska and the Noatak and Kobuk rivers in Northwestern Alaska, and to the coast thanks to prevailing sea currents and winds (Giddings, 1943(Giddings, , 1952aAlix, 2005; figure 1). Consequently, trees that produce the wood found on the Alaskan coast and in archaeological sites grew in various parts of Alaska and potentially elsewhere (Giddings, 1941;Eurola, 1971;Eggertsson, 1995;Alix & Brewster, 2004;Alix, 2005;Sander et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have highlighted that such assumptions can be incorrect, and a far wider extent of circumpolar sites must be considered during such processes, to accurately capture the potential history of samples (Hellmann et al, 2013). A recent combined assessment of radiocarbon and dendrochronological age estimates of Arctic driftwood samples found that radiocarbon dates from buried driftwood were in agreement with dendrochronological dating of modern beach ridge systems in coastal eastern Siberia (Sander et al, 2021), thus supporting the validity of age indications obtained from driftwood found on Holocene beaches.…”
Section: Using Driftwood To Infer Past Sea Ice Conditionsmentioning
confidence: 99%
“…It should be noted that these age determinations are for when the trees that these wood pieces were derived from died, rather than the date of a particular storm surge. It is well known that floated wood accumulating in coastal driftwood accumulations has long transit times from its source to where it is emplaced along the Beaufort coast (Eggertsson, 1994;Sander et al, 2021).…”
Section: Radiocarbon Datingmentioning
confidence: 99%